DECODING KEY OF THE TITLE AND DECORATIVE DESIGN IN THE NOVEL “THE HELP” OF KATHRYN STOCKETT - Чорній, Раїса (Current Issues of Foreign Philology, 2021)
The article deals with the characteristics of functioning of some elements of compositional privileged/strong positions of the text and their role in representing the specific features of the disclosure of the artist‟s conception of the text. The important prerequisite for the complete perception of the text is taking into consideration the peculiarities of the title and decorative design of the printed paper back and the appearance of the title page (front matter) of the printbook layout. The characteristics of the title complex as the tools for writer‟s intention realization in consideration of toleration to differences of opinion, beliefs, some ethnic stereotypes and racism hangovers in particular are analyzed on the sample of the novel “The Help” written by the American writer Kathryn Stockett. The plot creating function of the title is analyzed in this article, the following structural and semantic characteristics of the title of the book, its connection with the context of the fiction, its role in the plot developing and time and space continuum are highlighted in particular. The principle element enriching the artist‟s creation is its semantic peculiarity that plays the integral and concrete meanings. So at the beginning of the text the title is perceived by a reader as the text proprietary name represents the nominative, informative and prognostic functions, and after finishing reading the meaning of the title enriches in additional denotation. Visual contact with the book is one of the focal points in immediate connection with readers to represent a certain degree of interest and may provoke either positive or negative effect, willingness or refusal to continue further communication. Text information hidden in the illustration assists to show the main idea of the fiction, the pragmatics of writer‟s intent. The degree of coherence of cover illustration, the title of the book and the original is defined on the base of Kethryn Stockett‟s novel “The Help”. The difference between the decorative design of the book covers for the debut novel publications in the USA and Great Britain is characterized and the reasons of such choices are grounded.